The Practices and Problems of Teaching English Grammar to the Young EFL Learners - Rezwana, Maimana; Hossain, Md. Delowar; Ahmad, Saleh (International Journal of Language and Literary Studies, 2022)
English is the most widely used language (lingua franca) which is taught from primary to tertiary levels of education in Bangladesh education system. The secondary level is very much important for the young EFL learners to learn English language, especially grammar, as it prepares them and builds their foundation for the next levelsof education. However, this study attempts to assess the practices and problems of teaching English grammar in our country, especially the teaching approaches and techniques, the roles of teacher and learners, the perception of needs of English grammar, the learners’ preferences about the learning strategies etc. The data, which was collected through the teacher and student questionnaire, interviews of the teachers and classroom observations, has unveiled the problems in teaching English grammar to the students of class IX-X. The findings of the study suggest that the teachers prefer applying the memorization techniques rather than the communicative approach. It suggests specific measures to solve the problems of teaching grammar at the end of the paper.